2022
DOI: 10.1097/tp.0000000000004148
|View full text |Cite
|
Sign up to set email alerts
|

Ferret Lung Transplantation Models Differential Lymphoid Aggregate Morphology Between Restrictive and Obstructive Forms of Chronic Lung Allograft Dysfunction

Abstract: Background. Long-term survival after lung transplantation remains limited by chronic lung allograft dysfunction (CLAD). CLAD has 2 histologic phenotypes, namely obliterative bronchiolitis (OB) and restrictive alveolar fibroelastosis (AFE), which have distinct clinical presentations, pathologies, and outcomes. Understanding of OB versus AFE pathogenesis would improve with better animal models. Methods. We utilized a ferret orthotopic single-lung transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…We show that Krt14 and Krt15 expression in surface airway BCs functionally impacts proliferative potential and differentiation. Since Krt14 is upregulated in the SAE after injury, it likely demarcates transit-amplifying cells (8,(10)(11)(12)(13)(14). Transit-amplifying cells have a limited capacity to replicate and are primed to differentiate after a limited number of divisions (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We show that Krt14 and Krt15 expression in surface airway BCs functionally impacts proliferative potential and differentiation. Since Krt14 is upregulated in the SAE after injury, it likely demarcates transit-amplifying cells (8,(10)(11)(12)(13)(14). Transit-amplifying cells have a limited capacity to replicate and are primed to differentiate after a limited number of divisions (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others observed that Krt14 + cell abundance increases on the airway surface in multiple lung pathologies, such as in idiopathic pulmonary fibrosis, BO occurring after lung transplantation, restrictive allograft syndrome (RAS) after lung transplantation, and in injury models like SO 2 and Cl 2 gas exposure, and injuries caused by naphthalene and polidocanol exposure ( 8 , 10 14 ). It is unclear, however, whether Krt14 appearance in the SAE reflects migration and expansion of glandular progenitors that express Krt14 at baseline or a change within surface airway BCs to upregulate Krt14 expression.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on the novel work by Lynch et al 15 at the University of Iowa, it becomes clear that gaining an understanding of the underlying immunologic mechanisms of CLAD in the ferrets can lay the groundwork for improving both the treatment and knowledge of this disease. Nevertheless, challenges still exist in making this model the "mainstream workhorse" in our field.…”
mentioning
confidence: 99%